HEPATOPROTECTIVE EFFECT OF HEDYOTIS LESCHENAULTIANA DC, ETHANOL EXTRACT IN CCL 4 INDUCED HEPATOTOXICITY IN WISTAR RATS - Ps, Tresina; V, Sornalakshmi; K, Paulpriya; Vr, Mohan; K, Arumugasamy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The intention of this study is to explore the hepatoprotective potential of hepatoprotective potential of ethanol extract of Hedyotis leschenaultiana whole plant in carbon tetrachloride (CCl 4 ) induced hepatoprotective rats. Methods: Hepatotoxicity was induced in male wistar rats by intraperitoneal infection of CCl (2.5 ml/kg body weight for 14 days). The ethanol extract of H. leschenaultiana whole plant was administered to the experimental rats (100, 200, and 300 mg/kg body weight for 14 days). Silymarin (100 mg/kg) was given as a reference standard drug. In hepatotoxic rats, liver damage was studied by assessing parameters such as serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), serum alkaline phosphatase (ALP), total, conjugated and unconjugated bilirubin, gamma-glutamyl transferase, concentration of proteins, and antioxidants in serum. Results: Administration of hepatotoxins (CCl 4 4 ) showed significant elevation of SGOT, SGPT, serum ALP, total bilirubin, conjugated, unconjugated, and lipid peroxidation. Treatment with H. leschenaultiana (100, 200 and 300 mg/kg) significantly reduced the above-mentioned parameters. Regarding antioxidant activity, the ethanol extract of H. leschenaultiana exhibited a significant effect showing increasing levels of superoxide dismutase, catalase, glutathione peroxidase, reduced and glutathione, and glutathione reductase by reducing malondialdehyde levels. Conclusion: The ethanol extract of H. leschenaultiana have a significant effect on the CCl induced hepatotoxic animal models. Moreover, it is suggested that H. leschenaultiana can be used as a safe, cheap and effective alternative chemopreventive and protective against in the management of liver diseases. 4 Keywords: H. leschenaultiana, Bilirubins, Hepatotoxicity, Gamma-glutamyl transferase, Carbon tetrachloride, Melondialdehyde.